A robust estimate of the number and characteristics of persons released from prison in Australia. (25th February 2015) - Avery, Alex; Kinner, Stuart A.
Abstract Objective: To estimate the number and characteristics of adults released from prison in Australia. Method: We calculated ratios, stratified by age, sex and Indigenous status, by comparing the number of persons released from prison in New South Wales (NSW), with the number in NSW prisons on 30 June of the corresponding year. These stratified ratios were applied to Australia‐wide prison data to estimate the number and characteristics of persons released annually. Results: We estimated that in 2013, 38, 576 persons were released from prison in Australia − 25.3% more than the daily prison population. Young people, Indigenous people and women were over‐represented among those released. We estimated that 3.69 Indigenous women aged 18–24 were released annually for each equivalent person in prison; and 2.75 non‐Indigenous women aged 18–24 were released annually for each equivalent person in prison. Conclusions: The annual 'flow' through Australia's prisons is well in excess of the daily number, but information on those moving through prison systems is not yet publicly available. The characteristics of those released from prison differ meaningfully from those of people in prison. Routine, national reporting of prison separations is critical to informing upscaling and targeting of Throughcare services for this profoundly vulnerable population.